Case study of copper poisoning in a British dairy herd. Issue 1 (11th July 2013) - Bidewell, C. A.; Drew, J. R.; Payne, J. H.; Sayers, A. R.; Higgins, R. J.; Livesey, C. T.
Abstract : Following the initial diagnosis of chronic copper poisoning (CCP), the copper (Cu) status of a British dairy herd was investigated. Eight fatal cases of CCP were identified over a 17‐month period, from December 1999 to May 2001, involving seven Jersey cows and one Holstein‐Friesian; seven cows were dry when CCP occurred. Case diagnostic criteria were necrotising hepatopathy associated with abnormally high liver and kidney Cu concentrations. Analysis of the ration for the high‐yielding Jersey cow group revealed about 50 mg Cu/kg dry matter intake (DMI). Risk factors predisposing to fatal CCP were Jersey breed, previous high yield, first two weeks of the dry period and moderately high dietary Cu (greater than 40 mg Cu/kg DMI).